Adaptasi Pola Permainan Dangdut Gaya New Pallapa Pada Komunitas Pemusik Dangdut di Kec, Selo, Kab. Boyolali - Suranto, Suranto (Universitas Negeri Surabaya, 2024)
This study explores the adoption of the Pallapanan style of dangdut music by musicians and music communities in Selo, Boyolali District, Central Java. Originating from the